(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Acrylonitrile (AN) is a versatile monomer extensively utilized in the synthesis of copolymers with polyfunctional groups, imparting enhanced properties suitable for various applications. This article reviews the synthesis methods, reaction mechanisms, and applications of such copolymers, focusing on their structural characteristics and functional capabilities.